Análisis del proceso de inclusión educativa, en los departamentos de consejería estudiantil, en relación a la política y legislación vigente :Caso Colegio Victoria Bilingual Christian Academy, año lectivo 2013-2014 - Obando Ripalda, Cristina Rocío (2015)
If inclusive education is understood as a word game that has replaced the practice and conception of what was for years called integration, its essence in education is meaningless. To talk about inclusive education is to tear down social barriers and destroy established paradigms. It is to innovate in the human mind and provide teaching and learning alternatives beyond the curriculum and to transform the traditional educational methods and its exclusionary and marginalizing practices. This research only provides thin mist revealing the urgency to respond from a social and political perspective to the varied needs of the current educational system. It pretends to establish the conceptual and functional difference that involves talking about integration, special educational needs and inclusion. The attached investigation analyzes the current inclusive education policy in the Department of Student Counseling at the Victoria Bilingual Christian Academy, to determine the scope of the inclusion process, and the role played by the DECE. Talking about inclusive education certainly guarantees means to have the participation of children and adolescents and not just access to the institution. It is to look at others with respect and learn from their differences and embrace diversity. It is the assurance that learning is taking place and meaningful allowing to develop processes of tolerance, respect, equity and solidarity. Inclusive education generally is hinged to the State project of Good Living, where the main objective is focused on supporting the student´s multiple needs, launching the proposal of an inclusive approach that does not depend only on the DECE, but the mainly on the institutional vision and mission which requires teamwork and constant participation of the Community.